Upwelling di Laut Banda dan Pesisir Selatan Jawa serta Hubungannya dengan ENSO dan IOD - Herlina Ika Ratnawati; Rahmat Hidayat; Ahmad Bey; Tania June (Journal Omni-Akuatika, 2016)
Upwelling events analysis in southern coast of Java and Banda sea were conducted. The events were identified by using satellite data i.e. wind surface, Sea Surface Temperature (SST) and ocean color during period of 14 years (2002-2016) which calculated by Ekman pumping and Ekman transport. It’s found that Ekman pumping velocity in Banda Sea reached a maximum in June-July-August (JJA) by approximately 3,65x10 -6 . Comparing with Ekman transport, Ekman pumping makes an even greater contribution to the local upwelling in Banda Sea. Ekman pumping velocity in southern coast of Java reached a maximum in June-July-August (JJA) by approximately 4,9x10 -1 ms . Ekman pumping and Ekman transport makes an equal contribution to coastal upwelling in southern coast of Java. That’s related to highest clorophyll-a concentration apperars in JJA periode. Partial correlation analysis then was applied to identify a correlation between chlorophyll-a concentration and interannual climate variabilities such as ENSO and IOD. Partial Correlation between chlorophyll-a and Nino 3.4 and DMI-Dipole Mode Index (controlled) in Banda Sea is 0.18, and 0.05 in southercoast of Java. It’s represent ENSO (Elnino Southern Oscilation) has higher influences to Banda Sea than southern coast of Java. Partial correlation between chlorophyll-a and DMI and Nino 3.4 (controlled) is 0.55 in southern coast of Java, and 0.25 in Banda Sea. Its represent IOD (Indian Ocean Dipole) has higher influences to southern coast of Java than Banda Sea. Upwelling in Banda sea and along southern coast of Java dominantly occurs in southeast monsoon as a responds to regional wind driven motion associated with the monsoon climate. Various condition of chlorophyll-a booming also occured according to combination of ENSO and IOD events. -6 -1 msKeywords: upwelling, Banda sea, southern coast of Java, Ekman transport, Ekman pumping, IOD, ENSO